2017
DOI: 10.1017/s0033291717002471
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte telomere length and personality: associations with the Big Five and Type D personality traits

Abstract: BackgroundsAccelerated cellular ageing, which can be examined by telomere length (TL), may be an overarching mechanism underlying the association between personality and adverse health outcomes. This 6-year longitudinal study examined the relation between personality and leukocyte telomere length (LTL) across time among adults with a wide age-range.MethodsData from the Netherlands Study of Depression and Anxiety were used and included patients with a depression and/or anxiety disorder and healthy controls. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…However, many clinical studies pointing to a relationship between telomere length and either personality or age-related disease assess telomere length from blood samples, reporting leukocyte telomere length as a proxy measure for cellular aging 3 6 , 29 31 . The true meaning of such research relies upon the fundamental assumption that changes in telomere length are robust across tissues, and that leukocyte telomere length faithfully reflects tissues relevant to disease, such as the heart and brain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many clinical studies pointing to a relationship between telomere length and either personality or age-related disease assess telomere length from blood samples, reporting leukocyte telomere length as a proxy measure for cellular aging 3 6 , 29 31 . The true meaning of such research relies upon the fundamental assumption that changes in telomere length are robust across tissues, and that leukocyte telomere length faithfully reflects tissues relevant to disease, such as the heart and brain.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to obtain a more objective measure of the impact of personality on aging, more recent research has examined the link between personality and telomere length [3][4][5][6] . Telomeres, tandem repeat guanine-rich DNA sequences, are specialised protective caps located at the ends of eukaryotic chromosomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We had previously reported shorter TL among men and women who were more defensive in a study involving healthy participants [30]. Findings by Shoormans and colleagues [58] may provide additional insight into the mixed results regarding TL and personality traits. They found that while those with Type D personality (a construct related to defensiveness) had shorter TL at study onset, they were also less likely to show TL shortening over a period of 6 years compared to those without Type D. Protection from TL loss over time may have occurred via activation of telomerase [59].…”
Section: Discussionmentioning
confidence: 65%
“…Type D personality can also be described as a continuous trait, using the multiplicative interaction of SI by NA. Multiple biological (e.g., systemic inflammation, endothelial dysfunction, autonomic nervous dysregulation, telomere shortening) and behavioural (e.g., sleep problems, poor social support, poorer self-management skills) pathways are associated with Type D personality and may explain its adverse effects (Denollet et al 2018 ; Jandackova et al 2017 ; Kupper and Denollet 2018 ; Schoormans et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%